PENGARUH STRES KERJA, KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. SARANA AGRO NUSANTARA - Yohana Simanjuntak; Yuli Arnida Pohan (Jurnal Widya, 2024)
This research aims to determine the influence of work stress, leadership and organizational culture on employee performance at PT. Sarana Agro Nusantara. The number of research samples used in this research was 72 respondents. The data collection techniques used in this research used interviews, observation and questionnaires. The testing techniques used in the research are research instrument tests, descriptive statistical tests, classical assumption tests, multiple linear regression tests and hypothesis tests. The results of this research show that the work stress variable is accepted, meaning that the work stress variable has a positive and significant effect on employee performance, then also the leadership variable has a positive and significant effect on employee performance, the leadership variable has an effect on employee performance at PT. Sarana Agro Nusantara.